(3CTQa GdCfGe aj ehdO eUHGM GdXdGes - (3YHO GdhgGH Hf Ydj Hf YHO GdcGaj GdSHcj, CHh fUQ , JGL GdOjf , J (B771 (3g` s ((3YHOGdNGdb YHOGdNGdb ehSi s)
(3ChdgG (B:s
(3GdMeO ddg GdPj TQa GdCfGe HUGMH GdebGe GdCYdi, hced GdSYhO HCcQe ehdO Mhi TQakG haVdkG hedC GdhLhO HhLhOg YOdkG hhVYJg eNJhfkG eWgQkG ecMhdkG eYWQkG aj pNndY GdhbGQ hGdegGHI s
(3BNQgG (B:s
(3hSJQ GdYQT eSHhd YdjfG hYjf Gddg fGXQI EdjfG UdGI Gddg Ydi GdgGOj GdCejfG NJGe GdCfHjGA hGdeQSdjfG Je HYhf Gddg hMSf Jhajbg s
(3GdfSNI HgG MhGTs
(3HChdgG bUjOI YdjgG JGQjN SfI (B1289(3g`s
(3hHYV UaMGJgG eNJdaI GdJQJjHs
(3hgfGc Tc aj fSHI GdeNWhWI ddeDda s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B225s
Keywords: (3GdCOHs